PENGARUH PESTISIDA NABATI TERHADAP KEMATIAN LALAT RUMAH (MUSCA DOMESTICA) - Mauliku, Novie Elvinawaty (Jurnal Ilmu Kesehatan Immanuel, 2019)
House flies (Musca domestica) are a vector that caused diary so it needs to be controlled by using plant-based insecticide such as Lime (Citrus aurantifolia). Lime had active contains such as saponins, tannins, flavonoids and essential oils. This study was to impact of lemon juice to the death of house flies (Musca domestica). This study design is the True Experiment. The lime was defined  with three concentrations there are 25%, 27% and 29% of the death of house flies (Musca domestica) which is given three repetitions to 300 samples. Data was analyzed using univariate, bivariate used Kruskal Wallis and post hoc analysis used bonferonni tests to determine the effectiveness of concentration. The results found out that the percentage of dead houseflies (Musca Domestica) at a concentration of 25% on average by 53%, the concentration of 27% on average by 71% and 29% concentrations by an average of 92%. Statistical test results obtained that there are differences in various concentrations of lime juice to the death of house flies (Musca Domestica) with a p value (0.014). The effective concentration was at a 29% concentration against houseflies death 92%..